2012
DOI: 10.1111/j.1755-5949.2012.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

ABCC2 Polymorphisms and Haplotype are Associated with Drug Resistance in Chinese Epileptic Patients

Abstract: ABCC2-24C>T, 3972C>T polymorphisms and one ABCC2 haplotype is associated with AED resistance; ABCC2 1249G>A and ABCB1 3435C>T polymorphisms are not associated with AED resistance in our study. These data suggest that ABCC2 polymorphisms and haplotype may affect the response of antiepileptic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 37 publications
2
40
2
2
Order By: Relevance
“…for pharmacoresistance (Löscher and Potschka, 2002). A previous meta-analysis by Qu focused on the relation between ABCC2 polymorphisms and the risk of drug-resistant epilepsy in the Chinese population, and it concluded that ABCC2 C-24T and C3972T polymorphisms are associated with resistance to AEDs (Qu et al, 2012). This suggests that polymorphisms in genes encoding multidrug transporters may affect response to antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 98%
“…for pharmacoresistance (Löscher and Potschka, 2002). A previous meta-analysis by Qu focused on the relation between ABCC2 polymorphisms and the risk of drug-resistant epilepsy in the Chinese population, and it concluded that ABCC2 C-24T and C3972T polymorphisms are associated with resistance to AEDs (Qu et al, 2012). This suggests that polymorphisms in genes encoding multidrug transporters may affect response to antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies have reported an association between the ABCC2 rs2273697 and rs717620 polymorphisms and risk of drug-resistant epilepsy, but with conflicting results (Seo et al, 2008;Kwan et al, 2011;Hilger et al, 2012;Qu et al, 2012;Sporis et al, 2013;Subenthiran et al, 2013a;Escalante-Santiago et al, 2014;Ma et al, 2014). Qu et al (2012) revealed a significant association between the ABCC2 rs2273697 and rs717620 polymorphisms and resistance to antiepileptic drugs in Chinese epileptic patients.…”
Section: Discussionmentioning
confidence: 98%
“…Qu et al (2012) revealed a significant association between the ABCC2 rs2273697 and rs717620 polymorphisms and resistance to antiepileptic drugs in Chinese epileptic patients. Subenthiran et al (2013a) indicated a correlation between the ABCC2 rs2273697 and rs717620 polymorphisms and resistance to antiepileptic drugs in a study comprising 152 and 162 anti-epileptic drug-responsive and -resistant patients, respectively (Subenthiran et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…The patients were considered to be drug-responsive if they had not experienced any type of seizures for a minimum of 1 year after receiving AEDs. Drug resistance was defined as having at least four seizures during the previous year while trying at least three antiepileptic medications at maximal tolerated doses [31,32]. This study was performed according to the principles of the Declaration of Helsinki (revision of Edinburgh 2000).…”
Section: Subjectsmentioning
confidence: 99%